2007
DOI: 10.1508/cytologia.72.145
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Studies of Gametophytic Apomicts in Guinea Grass (Panicum maximum) II. Characteristics of Aposporous Initial Cell-derived Embryo Sac

Abstract: SummaryThe ultrastructural analysis using ultra-thin section and transmission electron microscope was carried out to characterize the features of the reproductive cells in aposporous initial cell (AIC)-derived embryo sac (AES), i.e. egg, synergid and polar cells, in ovule of facultative apomictic Panicum maximum. At anthesis, the first AES located in micropylar end consists of egg apparatus with 2 synergids and 1 egg cell, and the central cell with 1 nucleus. The other AESs contain less than four cells. The eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, it is considered that nucellar cells located in chalazal end inherit and develop dominantly when they sense some signals from sexual ones which will be the fate of abortion and degeneration, and/or lose capacity of division. At the same time, one of nucellar cell-derived AIC cells appears, sexual cells and other nucellar cells provide nutrients for AIC differentiation (Guan et al 2006(Guan et al , 2007(Guan et al , 2008. In some meanings, the life of the ovule (or ovary) will be kept by whatever either sexual or asexual (nucellar) cell becomes to embryo sac.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…However, it is considered that nucellar cells located in chalazal end inherit and develop dominantly when they sense some signals from sexual ones which will be the fate of abortion and degeneration, and/or lose capacity of division. At the same time, one of nucellar cell-derived AIC cells appears, sexual cells and other nucellar cells provide nutrients for AIC differentiation (Guan et al 2006(Guan et al , 2007(Guan et al , 2008. In some meanings, the life of the ovule (or ovary) will be kept by whatever either sexual or asexual (nucellar) cell becomes to embryo sac.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Recently, very interesting hypothesis was proposed that some apomictic species from the Compositae family (genera Chondrilla , Taraxacum ) have synergids only in the juvenile phase, which lacks a filiform apparatus, and that this is connected with apomixis (Kościńska-Pająk 2006 ; Kościńska-Pająk and Bednara 2006 ). There are, however, arguments against this idea because other studies of apomictic species from other families showed the occurrence of the filiform apparatus (e.g., Jankun 1994 ; Guan et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have reported that the most different event between the sexual and apomictic plants was the appearing of aposporous embryo sac initial cell (AIC) following the degeneration of the mature haploid megaspore in guineagrass (Panicum maximum). This was observed by Normarski differential interference-contrast microscopy (DIC), and transmission electron microscopy (TEM) [5][6][7][8]. And according to the above results, the authors have obtained the apomixis-specific gene, named as ASG-1, from facultative apomict of guineagrass, using the differential screening method based on the ovary length as an index [9,10].…”
Section: Introductionmentioning
confidence: 83%